PERANCANGAN PERANCANGAN PROTOTYPE KARTU PELAJAR CERDAS DI MA INSAN KAMIL KOTA SORONG BERBASIS RFID - Ery Murniyasih; Alexander Jamlean (Politeknik Bisnis Indonesia, 2021)
The purpose of this study is to optimize the use of student cards owned by students, to perform automatic student attendance and as a student's school exam card each semester. The method used is to integrate three main parts, namely the RFID System (cliet), Gateway System, and Server. The designed student card contains a UID (RFID Tag) which is read by an RFID reader every time students enter class for attendance and also when taking school exams. The RFID tag will be data that will be forwarded to Arduino Mega as a data processor and forwarded through the System Gateway to a server in the form of an orange pi so that it can be monitored by the operator. The test results for 5 times the test, the average response time for network access and getting the IP address from the router is 16.6 seconds, the average time the device responds to active student RFID card data from the database is 2.6 seconds. The average time of student's RFID card access to the device to the web server application is 3.8 seconds